The preparing pupils for textile technology Olympiads: Teaching design and technology in basic education school context - Urdziņa-Deruma, Māra (FormAkademisk, 2023)
This article presents how design and technology teachers teach pupils who successfully participate in Open Design and Technology Olympiads (textile technology). After interviewing twelve teachers and performing qualitative content analysis it is concluded that several personality traits are crucial for teachers, for pupils to succeed in the competition: competence, consistent work, and continuous development. An appreciation of school management is also important. In the teaching process, teachers should use self-made materials and varied sources, pay attention to creating ideas, experiment with materials and techniques, and think about products’ usage, composition, and technical quality by using both regular and different forms of extracurricular lessons in an inspiring environment. Individual work with each pupil is vital. Teachers have different approaches to the process of idea generation.